2005
DOI: 10.1111/j.1365-2966.2005.09032.x
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear evolution of suppressed dark matter primordial power spectra

Abstract: We address the degree and rapidity of generation of small‐scale power over the course of structure formation in cosmologies where the primordial power spectrum is strongly suppressed beyond a given wavenumber. We first summarize the situations where one expects such suppressed power spectra and point out their diversity. We then employ an exponential cut‐off, which characterizes warm dark matter (WDM) models, as a template for the shape of the cut‐off and focus on damping scales ranging from 106 to 109 h−1 M⊙.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 22 publications
1
56
0
Order By: Relevance
“…In this case the resulting mass range is at most 1.8 eV ≤ m ≤ 53 eV, where the upper bound scales linearly with g s ef f (T Dec ). In figure 13 we show the combined results on g A free streaming mass of more than ∼ 10 9 solar masses is excluded for warm dark matter as found by [41]. The region excluded by this constraint is the area with the vertical pattern.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In this case the resulting mass range is at most 1.8 eV ≤ m ≤ 53 eV, where the upper bound scales linearly with g s ef f (T Dec ). In figure 13 we show the combined results on g A free streaming mass of more than ∼ 10 9 solar masses is excluded for warm dark matter as found by [41]. The region excluded by this constraint is the area with the vertical pattern.…”
Section: Discussionmentioning
confidence: 74%
“…One can see here that the velocity dispersion (or the speed of sound) drops like for an ordinary warm dark matter scenario (Ref. [40,41,44,45]) contrary to the generalized Chaplygin gas which has a late time growing speed of sound. Now inserting the velocity dispersion into eq.…”
Section: Linear Structure Formationmentioning
confidence: 76%
“…One is the quick regeneration of the suppressed power of WDM models and the catching up with the linear and non-linear power of the CDM models (Boehm et al 2005;Schneider et al 2012). This effect might make WDM models difficult to exclude using QSO-galaxy lensing systems.…”
Section: Introductionmentioning
confidence: 99%
“…The general assumption is that DM consists of cold, massive particles (CDM). However, recent work has shown that small couplings with Standard Model particles (in particular, neutrinos [5][6][7][8][9], photons [10][11][12][13] and baryons [14][15][16]) cannot yet be ruled out using cosmological data alone and are indeed expected in several extensions of the Standard Model e.g. Refs.…”
Section: Introductionmentioning
confidence: 99%